2011
DOI: 10.1097/phh.0b013e3181fd4d19
|View full text |Cite
|
Sign up to set email alerts
|

Piloting Performance Measurement for Comprehensive Cancer Control Programs

Abstract: This pilot test of the performance measures worksheet established the feasibility of conducting a standardized survey of CCC programs to identify issues of importance to developing and implementing the CCC program at national and program levels. The performance measures provided unique data on CCC grantees to the CDC funders and feedback on performance measures for improving questions on future surveys. Refinement of the performance measures will provide a tool for monitoring processes of action and accountabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In their analysis, 60% of programs reported that their partners had implemented at least one priority strategy from their jurisdiction’s cancer control plan from June 2008 through June 2009. Rochester and colleagues, in their pilot test of a 2007 NCCCP grantee performance measurement worksheet, also reported that 60% of programs indicated that their partners had implemented interventions ( 25 ). These discrepancies may be related to the fact that we asked CCC program directors to refer partners who collaborate with them in the selection and use of EBPs, thus providing us with a sampling pool more likely to include partners involved with implementation.…”
Section: Discussionmentioning
confidence: 99%
“…In their analysis, 60% of programs reported that their partners had implemented at least one priority strategy from their jurisdiction’s cancer control plan from June 2008 through June 2009. Rochester and colleagues, in their pilot test of a 2007 NCCCP grantee performance measurement worksheet, also reported that 60% of programs indicated that their partners had implemented interventions ( 25 ). These discrepancies may be related to the fact that we asked CCC program directors to refer partners who collaborate with them in the selection and use of EBPs, thus providing us with a sampling pool more likely to include partners involved with implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Development and pilot testing of the NCCCP performance measurement system has been described previously. 17 In 2008, the NCCCP performance measurement system was refined to clarify survey questions and strengthen indicators to more accurately measure activities and outcomes. Additional refinement of the survey occurred in 2009 and 2010 in response to program directors’ and program staff feedback and the need to collect data for emerging programmatic processes.…”
Section: Methodsmentioning
confidence: 99%
“…In 2007, a set of performance measures was developed and pilot tested with 61 NCCCP awardees 17 to measure performance in the five-year funding cycle spanning 2007-2012. To begin the process, data were systematically collected across all awardees to describe attributes of the NCCCP to invested stakeholders, document current progress, and foster quality improvement.…”
Section: Introductionmentioning
confidence: 99%
“…All these factors influence the level of funding each participant receives from CDC. Evaluation efforts at the national level in the early years of the program, including the development and fielding of a performance measurement system and cancer plan assessment tool, provided valuable information regarding technical assistance needs and improvements that could be made across all participants [16][17][18]. Results from surveys in 2009 and 2010 showed that a majority of programs had successfully implemented at least one community-or organization-level change strategy; however, not all programs were using only evidence-based interventions, and there were few participants linking their activities to cancer impact [19].…”
Section: The National Comprehensive Cancer Control Programmentioning
confidence: 99%